Muhammad Asad’s the message of the Qur’an - Ahmad, Nadzrah; Amir, Ahmad Nabil (Horizon Research Publishing Corporation, 2016)
This paper aims to analyze the method of Qur’anic hermeneutic (al-ta’wil) as set forth by Muhammad Asad in his magnum opus, The Message of the Qur’an. Its objective is to study the underlying method he crafted in the commentary and the influence it projected in the Muslim world. The study of Muhammad Asad’s method is crucial to gain an understanding of his modern worldviews, and the underlying pattern of scientific and rational thought grounded in his work, which reflected the renewal project of Islam advocated by Shaykh Muhammad Abduh and Sayid Muhammad Rashid Rida in Tafsir al-Manar.